EFEKTIVITAS IMPLEMENTASI MIGRASI KARTU TANDA PENDUDUK DIGITAL DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN OKU TIMUR, SUMATERA SELATAN - Winda Astuti; Irfan Setiawan (Institut Pemerintahan Dalam Negeri, 2024)
Technological advances have brought about the development of digital transformation one of which is in the field of population administration, namely through the presence of DigitalPopulation Identity Cards (KTP). The East Oku Regency Population and Civil Registration Service has implemented digital-based Population Identity Cards (KTP) since 2023, but in implementation there are still several obstacles. Therefore, analysis is needed to assess the effectiveness of the implementation of the Digital Identity Card (KTP), as well as to analyze theprocesses and factors that influence the success of the effectiveness of the Digital Identity Card (KTP) program at the East Oku Regency Population and Civil Registration Service office. This research uses descriptive qualitative research methods, data collection techniques by means of observation, and literature study. The research results show that the implementation of population administration is quite effective in terms of the dimensions of usefulness, convenience and acceptance of information technology, although there are obstacles in terms ofdirect socialization because not all residents of East Oku Regency know about the implementation of digital KTP socialization. This especially applies to older people who do notunderstand technology so they have difficulty using IKD.